The Effect Of Internet Use On Political Participation: Could The Internet Increase Political Participation In Thailand? - Meesuwan, Sanyarat (Penerbit Universiti Sains Malaysia (USM Press), 2016)
The Internet, as part of information and communication technology, provides citizens with access to information, and allows them to interact with others in online communities. It could also increase the users' political potentials by decreasing the costs and resources' restraints. Given these benefits, this research asks whether or not Internet use would increase political participation in Thailand. Using the 2010 Asian Barometer data conducted in Thailand, the relationship between Internet use and political participation was tested. The results indicate that Internet use positively correlated with political participation, after controlling for individual resource measurement, namely demographic characteristics, education attainment, socio-economic status, political efficacy, and organisational skills. The odds of the respondents, who used the Internet to contact news media to solve their problems with government officials or policies, and to get together with others to raise an issue or sign a petition, were greater than those who did not use the Internet. The findings suggest that the Internet had mobilised people to actively engage in political participation. Policy recommendations aiming at promoting Internet use to encourage political participation and to strengthen the Thai democratic system as a whole are listed at the end of the research.